Transcriptome analysis in Parhyale hawaiensis reveal sex-specific responses to AgNP and AgCl exposure - Artal, Mariana Coletty; Pereira, Karina Danielle [UNESP]; Luchessi, Augusto Ducati [UNESP]; Okura, Vagner Katsumi; Henry, Theodore Burdick; Marques-Souza, Henrique; Umbuzeiro, Gisela de Aragao (Elsevier B.V., 2020)
Analysis of the transcriptome of organisms exposed to toxicants offers new insights for ecotoxicology, but further research is needed to enhance interpretation of results and effectively incorporate them into useful environmental risk assessments. Factors that must be clarified to improve use of transcriptomics include assessment of the effect of organism sex within the context of toxicant exposure. Amphipods are well recognized as model organisms for toxicity evaluation because of their sensitivity and amenability to laboratory conditions. To investigate whether response to metals in crustaceans differs according to sex we analyzed the amphipod Parhyale hawaiensis after exposure to AgCl and Ag nanoparticles (AgNP) via contaminated food. Gene specific analysis and whole genome transcriptional profile of male and female organisms were performed by both RT-qPCR and RNA-seq. We observed that expression of transcripts of genes glutathione transferase (GST) did not differ among AgCl and AgNP treatments. Significant differences between males and females were observed after exposure to AgCl and AgNP. Males presented twice the number of differentially expressed genes in comparison to females, and more differentially expressed were observed after exposure to AgNP than AgCl treatments in both sexes. The genes that had the greatest change in expression relative to control were those genes related to peptidase and catalytic activity and chitin and carbohydrate metabolic processes. Our study is the first to demonstrate sex specific differences in the transcriptomes of amphipods upon exposure to toxicants and emphasizes the importance of considering gender in ecotoxicology. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Amphipod; Gene expression; Glutathione-S-Transferase; RNA-Seq; RT-qPCR